Development Strategy of Noken Product on Local Community in Sota Merauke - Batlajery, Semuel; Setya Wati, Caecilia Heny (Universitas Pendidikan Ganesha, 2019)
This research aims to formulate Strategy development product Noken of to local community of district border of Merauke / Papua New Guinea. The method used is the observation and in-depth interview on noken craftsmen. The formulation of appropriate strategies for local communities Noken craftsmen are essential for business continuity and profit in business competition.Increasingly tight competition required the noken craftsmen to always do the strategy in developing noken products well.Moreover, neighboring Papua New Guinea's noken products are always flooding the sota border areas.Analysis SWOT shows that the position of noken craftsmen in the tourist area means the situation is very profitable.Craftsmen have the opportunity and power so as to harness the power to redeem opportunities.